Diagnostic Accuracy of Resistive Index of Doppler Ultrasound in Diagnosing Malignant Ovarian Tumors, Taking Histopathology as Gold Standard - Ibrahim, Sadaf; Majeed, Sajida; Ahsan, Hafiz Haseeb; Khan, Adeela Sarfraz; Abdulmajeed, Sadia; Mushtaq, Azka (Biological and Clinical Sciences Research Journal, 2025)
Ovarian cancer remains a leading cause of gynecologic malignancy-related mortality worldwide due to delayed diagnosis and nonspecific clinical presentation. Differentiating benign from malignant ovarian tumors preoperatively is essential for optimal patient management and surgical planning. Doppler ultrasound, particularly the assessment of resistive index (RI), has emerged as a valuable, non-invasive diagnostic tool for evaluating adnexal masses. Objective: To determine the diagnostic accuracy of the resistive index of Doppler ultrasound in diagnosing malignant ovarian tumour, taking histopathology as the Gold standard. Methodology: This cross-sectional study was conducted at Sheikh Zayed Hospital’s radiology department from September 2024 to February 2025. It involved patients presenting with adnexal masses on ultrasound, following ethical approval and informed consent. A sample size of 110 was determined based on a 95% confidence level, with a focus on malignant ovarian tumors. Inclusion criteria included patients aged 20 to 60 years, with a disease duration exceeding three months and specific ultrasound characteristics. Patients with simple cysts, metabolic disorders, and prior anti-tumor treatments were excluded. Each subject underwent Doppler sonography, and the resistive index (RI) was measured to differentiate between benign and malignant tumors. Surgical samples were analyzed histopathologically to confirm diagnoses. Data were recorded using a proforma and analyzed with SPSS 25.0, focusing on diagnostic accuracy, sensitivity, and specificity of the Doppler ultrasound findings compared to histopathology results. Stratification was applied based on age, disease duration, and other variables. Result: In our study, the mean age of patients was 39.08 years, with a disease duration of 20.27 months and average lesion sizes of 10.48 mm. Among participants, 70.8% had benign tumors and 29.2% malignant, with significant differences noted in marital status. Doppler color ultrasound identified 75.5% of lesions as benign and 24.5% malignant, yielding a sensitivity of 80% and specificity of 91.76%. Notably, benign tumors averaged 8.18 mm, while malignant ones were larger at 17.55 mm (p-value 0.00). Conclusion: Doppler ultrasound, particularly resistive index, effectively differentiates benign from malignant ovarian tumors, with a sensitivity of 80% and specificity of 91.76%. Younger women tend to have benign lesions, while older, postmenopausal women are at higher risk for malignancy, making this tool vital for early screening.